NPK Fertilizer Application for Enhanced Productivity of FARO 44 Lowland Rice in Guinea Savanna Zone of Nigeria - Agbo, C (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
A field study was conducted to assess the effects of NPK (20:10:10) fertilizer on the performance of FARO 44 lowland rice at two sites in Yaba and Gada Biyu in the southern guinea savanna of Nigeria in 2019 cropping season. At both sites, the experiment was laid out in a randomized complete block design (RBCD) with three replicates. The treatments were five NPK (20:10:10) fertilizer levels (0,100,200,300 and 400kg/ha). Data collected were subjected to analysis of variance (ANOVA) using the GenStat (2011) statistical package. Means were separated using Least Significant Difference (LSD) at 5% probability level. The meteorological data from both locations recorded unimodal rainfall distribution but the soil at Yaba was a clay soil with high organic matter, nitrogen, phosphorus, calcium and magnesium contents, while the soil at Gada Biyu had low nitrogen, phosphorus and potassium contents. NPK fertilizer significantly increased rice plant height, number of tillers per plant, number of leaves per plant, panicle length, panicle weight, number of grains per panicle and 1000-grain weight in the two sites. Grain yield also followed a linear response to NPK fertilization up to 400kg/ha. Grain yield at Yaba was 21.6% significantly higher than the yield at Gada Biyu which had lower soil fertility than the former. Therefore, to optimize the growth and yield of FARO 44 lowland rice, applying NPK fertilizer at 400kg/ha could be recommended for farmers.